Gleichzeitigkeit in der Interaktion Strukturelle (In)Kompatibilität bei Multiaktivitäten in Theaterproben - Krug, Maximilian (Linguistik - Impulse & Tendenzen, 2022)
By taking a conversation-analytical approach, this study uses mobile eye tracking and audiovisual recordings of theater rehearsals to examine how people who are interacting with each other simultaneously coordinate relevant activities. Of special significance is the structural compatibility of the modes of participation in the co-relevant activities, as different methods of coordination are used depending on the degree of (in-)compatibility.